Small-Sample Properties of Estimators of Regression Coefficients Given a Common Pattern of Missing Data - Conniffe, Denis (Review of Economic Studies, 1983)
For a commonly occurring pattern of missing data, estimators of regression coefficients are derived by a non-likelihood method. The small-sample properties are investigated for the case of normality assumptions. The estimators are shown to be unbiased, exact small-sample variance formulae are derived, comparisons are made with ordinary least-squares estimators and it is demonstrated that the estimators can be more efficient than maximum-likelihood estimators in small samples.